Comment on "New Exact Solutions to the KdV-Burgers-Kuramoto Equation with the Exp-Function Method". (24th February 2014) - Liu, Hong-Zhun
Abstract : We point out in this paper that the claims made by Kim et al. in the commented paper are incorrect and no new exact solution was obtained.